Streamlined life cycle inventory of dental syringes manufacturing - Munhoz, C. R.; Almeida, C. M. V. B.; Agostinho, F.; Bonilla, S. H.; Giannetti, B. F. (Journal of Environmental Accounting and Management, 2026)
Among the methods proposed to environmental management of productive activities, Life Cycle Assessment is one of the most integrated, complete and effective. The product assessed is the dental Carpule syringe. The aim of this work is to achieve a Streamlined Life Cycle Inventory (LCI) to quantify the electric energy consumption and the solid waste release from dental Carpule syringes manufacture. The methodological framework is based on ISO 14040/2006. The LCI covers the syringe life cycle from mining to disposal. The limits of the system include the stages of copper and zinc mining and ore beneficiation, the production of polyethylene used for syringe and needle packing, the production of steel for needles and syringe coils, and the use of the whole set by dentists. The functional unit was defined as 106 (one million) applied anesthesia. During improvement assessment, the proposed solutions allow reducing the energy consumption at about 20% in the manufacturing stage. The solid waste quantity may be reduced by almost 40 % in the manufacturing stage, equivalent to approximately 6.5 % of the total solid waste released during the entire life cycle of the Carpule dental syringe.